REPOTENCIACIÓN DE FORMA INCLUSIVA DE LOS ATRACTIVOS Y SERVICIOS TURÍSTICOS DE LA CENTRAL EÓLICA VILLONACO DE LA CIUDAD DE LOJA - CORONEL LÓPEZ, SHEILA DENISSE (2019)
For the development of the research, a general objective was set up: "To provide an inclusive replenishment of the tourist attractions and services of the Villonaco Wind Power Plant in the city of Loja" and three specific objectives. "Make a tourist diagnosis of the current situation of the Villonaco Wind Power Plant in the City of Loja", knowing the reality of the place of study and the areas of influence of it, is a fundamental part to know if tourism can develop properly , to achieve this objective, the combination of internal factor methodologies was used to know the current situation of Central Eólica Villonaco and the external factors to analyze how the places that represent the zone of influence of the Central are located, information presented with the help of the diagnosis card of Carla Ricaurte localities, this analysis presented us with general data, tourist data and information on basic services, in addition to a market study and the presentation of a profile of tourists information that was presented through surveys conducted to people who have visited Central, a SWOT analysis built with on the help of interviews and direct observation that after its presentation leads us to a matrix of strategies and based on the SENPLADES format that follows the project shows a problem tree and objectives tree that allow defining the actions to be taken to mitigate the problems presented. “Prepare a proposal for the Tourism Development of the Villonaco Wind Power Plant", with the diagnosis made, a model of options was created that can be used to improve the visits of tourists with disabilities or without it to the Central here through the frame matrix Logical activities are shown with planning, operation and costs of the activities, the technical feasibility of each of the proposed activities is presented to adequately analyze how to execute them, and finally present the social and environmental impacts that the implementation of the project would produce. "Propose the implementation strategies for the Tourism Development of the Villonaco Wind Power Plant", in this objective the schedule of activities to be carried out is established, the budget to be valued by the entity that will execute the project and the financial and economic-social evaluation, the execution, promotion, monitoring and evaluation strategies of the project that allow determining if it is viable. The results found based on the research showed, in the diagnosis that El Tambo parish does not have an adequate infrastructure to make tourism dynamic in that place, however it has some important natural tourist attractions that are currently visited by local tourists , to obtain relevant information on tourism services, the population closest to the parish was 5 taken into account, giving us information about the canton of Catamayo; on the other hand, the Sucre parish, being the largest parish in the city of Loja, has better tourist services, better conditions to boost tourism in the sector, this study was conducted in these places based on the location of the Central. The second objective presented results for tourism development, highlighting the importance of adapting the different facilities of the Interpretation Center, training the staff of the Villonaco Wind Power Plant and creating tourism packages for the areas of influence, so that together with the creation of an inclusive tourism, also achieve to promote tourism in the places close to the project to generate economy and sources of employment, which should be disseminated through official channels for the knowledge of the community. Finally, the strategies presented will allow each of the activities to be adequately developed, verifying the time for its implementation, the cost per activity, the social and environmental sustainability and the financial and economic-social evaluation of the project. In conclusion, the "Repowering of the Villonaco Wind Power Plant" contributes to the area of influence to the development of tourist activity and therefore to the generation of employment sources generating development in the areas of influence, additionally it will allow the Wind Power Plant Villonaco, As an emblematic project, it is a pioneer in adapting its facilities to improve the visit of people with hearing, visual and physical disabilities to attractiveness, which will generate both economic and social benefits for all persons with disabilities.